Determining Residential Location Choice along the Coastline in Victoria Island, Nigeria Using a Factor Analytical Approach - Ayoola A.B.; Oyetunji A.K.; Amaechi C.V.; Olukolajo M.A.; Ullah S.; Kemiki O.A. (MDPI, 2024)
This paper evaluates how households consider environmental attributes alongside other housing attributes in their residential location decisions along the coastline in Victoria Island, Nigeria. The data were obtained from tenants revealed preference surveys where 204 respondents rated 15 identified and most common key factors in the order by which they influence their residential location choices. The factor analytical approach was then applied to understand how these factors influence such decisions. Thus, this study also gives bearing to the factors considered in making policy and/or investment decisions around residential location choice (RLC). The results revealed the presence of four key components with a total variance of 70.76%. Among the components, neighbourhood, critical dwelling cum socio-economic attributes are found to have a significant influence in explaining 39.78% of the variation in the factors influencing the study areas selection as the residential location choice (RLC) for households. The findings have implications for households residential location choices. For residential locations to be equally attractive to tenants, policymakers and urban planners should pay attention to addressing the menace of the neighbourhoods including crime and traffic congestion. Moreover, property owners should respond to tenants needs by paying attention to the provision of utility facilities such as portable water and an appropriate mix of toilet/bathrooms to available bedrooms. 2023 by the authors.